PENGARUH PERAN GANDA, STRES KERJA TERHADAP KINERJA ASN WANITA MELALUI KEPUASAN KERJA DI LINGKUNGAN PEMERINTAH KOTA TARAKAN - Nova Susanti; Syahran Syahran; Salahuddin Salahuddin; Erick Karunia (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2025)
Abstract. Dual role conflict and work stress have become global issues in the public sector, affecting productivity, psychological resilience, and the quality of services provided by government employees. In Indonesia, particularly in local government institutions such as the Government of Tarakan City, administrative demands, high workloads, and the dynamics of public service increasingly elevate the risk of role conflict and work stress, which ultimately can reduce job satisfaction and the performance of civil servants. This phenomenon underscores the importance of research to identify how role pressures and stress influence the performance of public officials within the context of local bureaucracy. This study aims to analyze the influence of dual role conflict and work stress on the performance of civil servants, as well as examine the role of job satisfaction as a mediating variable in this relationship. By integrating perspectives from role theory and work stress theory, this research seeks to provide a deeper understanding of the psychological mechanisms that affect the performance of public sector employees. The research method uses a quantitative approach with a survey conducted among civil servants of the Government of Tarakan City. Data were analyzed using Structural Equation Modeling (SEM) to test the direct and indirect relationships between variables. Variable measurements used standardized instruments that have been validated in various previous studies. The results show that dual role conflict has a positive effect on work stress and indirectly decreases the performance of civil servants through reduced job satisfaction. In addition, work stress has a significant influence on employee satisfaction and performance. Job satisfaction plays a partial mediating role in the relationship between work stress and performance, emphasizing the importance of psychological aspects as key mechanisms determining civil servant productivity. These findings provide implications for local governments to design stress management policies, employee welfare programs, and interventions that support role balance, so that job satisfaction and civil servant performance can be sustainably improved.